\(\frac{4x}{x^2+4x+3}-1=6\left(\frac{1}{x+3}-\frac{1}{2x+2}\right)\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
b, \(\frac{1}{x-1}-\frac{5}{x-2}=\frac{15}{\left(x+1\right)\left(2-x\right)}\left(ĐKXĐ:x\ne\pm1;x\ne2\right)\)
\(\Leftrightarrow\)\(\frac{1}{x-1}+\frac{5}{2-x}=\frac{15}{\left(x+1\right)\left(2-x\right)}\)
\(\Leftrightarrow\)\(\frac{\left(x+1\right)\left(2-x\right)+5\left(x-1\right)\left(x+1\right)}{\left(x+1\right)\left(2-x\right)\left(x-1\right)}=\frac{15\left(x-1\right)}{\left(x-1\right)\left(x+1\right)\left(2-x\right)}\)
Suy ra:
\(\Leftrightarrow\)(x+1)(2-x)+5(x-1)(x+1) = 15(x-1)
\(\Leftrightarrow\)2x-x2-x+2+5x2-5 = 15x-15
\(\Leftrightarrow\)2x-x2-x+5x2-15x = -15+5-2
\(\Leftrightarrow\)4x2-14x = -12
\(\Leftrightarrow4x^2-14x+12=0\)
\(\Leftrightarrow4x^2-8x-6x+12=0\)
\(\Leftrightarrow\)4x(x-2) - 6(x-2) = 0
\(\Leftrightarrow\left(x-2\right)\left(4x-6\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-2=0\\4x-6=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=2\left(kotm\right)\\x=\frac{3}{2}\left(tm\right)\end{matrix}\right.\)
Vậy pt có nghiệm duy nhất x = \(\frac{3}{2}\)
ĐKXĐ: \(x\ne\left\{-3;-1\right\}\)
\(\Leftrightarrow\frac{-x^2-3}{\left(x+1\right)\left(x+3\right)}=\frac{6\left(x+1\right)-3\left(x+3\right)}{\left(x+1\right)\left(x+3\right)}\)
\(\Leftrightarrow-x^2-3=6x+6-3x-9\)
\(\Leftrightarrow x^2+3x=0\Rightarrow\left[{}\begin{matrix}x=0\\x=-3\left(l\right)\end{matrix}\right.\)
\(\frac{4x}{x^2+4x+3}-1=6\left(\frac{1}{x+3}-\frac{1}{2x+2}\right)\) \(ĐK:x\ne-1;x\ne-3\)
\(\Leftrightarrow\frac{4x}{x^2+4x+3}-\frac{x^2+4x+3}{x^2+4x+3}=6\left[\frac{2\left(x+1\right)}{2\left(x+3\right)\left(x+1\right)}-\frac{x+3}{2\left(x+1\right)\left(x+3\right)}\right]\)
\(\Leftrightarrow\frac{4x-x^2-4x-3}{x^2+4x+3}=6\left[\frac{2\left(x+1\right)-x-3}{2\left(x+3\right)\left(x+1\right)}\right]\)
\(\Leftrightarrow\frac{-x^2-3}{x^2+4x+3}=6\left[\frac{2x+2-x-3}{2\left(x^2+4x+3\right)}\right]\)
\(\Leftrightarrow\frac{-x^2-3}{x^2+4x+3}=\frac{6\left(x-1\right)}{2\left(x^2+4x+3\right)}\)
\(\Leftrightarrow\frac{-x^2-3}{x^2+4x+3}=\frac{3\left(x-1\right)}{x^2+4x+3}\)
\(\Leftrightarrow-x^2-3=3x-3\)
\(\Leftrightarrow-x^2-3x=0\)
\(\Leftrightarrow-x\left(x+3\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\x=-3\left(loại\right)\end{cases}}\)
Vậy x = 0
\(ĐK:x\ne\frac{-1}{2};x\ne\frac{-3}{2}\)
\(\frac{3}{2x+1}=\frac{6}{2x+3}+\frac{8}{4x^2+8x+3}\)
\(\Leftrightarrow\frac{3}{2x+1}-\frac{6}{2x+3}=\frac{8}{4x^2+8x+3}\)
\(\Leftrightarrow\frac{3\left(2x+3\right)-6\left(2x+1\right)}{\left(2x+1\right)\left(2x+3\right)}=\frac{8}{4x^2+8x+3}\)
\(\Leftrightarrow\frac{6x+9-12x-6}{4x^2+8x+3}=\frac{8}{4x^2+8x+3}\)
\(\Leftrightarrow-6x+3=8\)
\(\Leftrightarrow x=-\frac{5}{6}\)
Vậy ...
\(\frac{4x}{x^2+4x+3}-1=6\left(\frac{1}{x+3}-\frac{1}{2x+2}\right)\)đkxđ \(x\ne-1;-3\)
\(\Leftrightarrow\frac{4x}{x^2+4x+3}-\frac{6}{x+3}+\frac{3}{x+1}=1\)
\(\Leftrightarrow\frac{4x-6x-6+3x+9}{\left(x+1\right)\left(x+3\right)}=1\)
\(\Leftrightarrow\frac{x+3}{\left(x+3\right)\left(x+1\right)}=1\)
\(\Leftrightarrow\frac{1}{x+1}=1\)
\(\Leftrightarrow x+1=1\)
\(\Leftrightarrow x=0\left(tm\right)\)
\(\frac{4x}{x^2+4x+3}-1=6\left(\frac{1}{x+3}-\frac{1}{2x+2}\right)\)
\(\frac{4x}{\left(x+1\right)\left(x+3\right)}-1=6\left(\frac{1}{x+3}-\frac{1}{2x+2}\right)\)
\(\frac{4x}{\left(x+1\right)\left(x+3\right)}-1=6\left(\frac{1}{x+3}-\frac{1}{2x-2}\right)\)
\(4x-\left(x+1\right)\left(x+3\right)=6\left(\frac{1}{x+3}-\frac{1}{2\left(x+1\right)}\right)\left(x+1\right)\left(x+2\right)\)
\(-x^2-3=\frac{6x^2}{x+3}+\frac{24x}{x+3}+\frac{18}{x+3}-\frac{3x^2}{x+1}-\frac{12x}{x+1}-\frac{9}{x+1}\)
\(-x^4-4x^3-6x^2-12x=3x^3+9x^2-3x\)
\(-x^4-4x^3-6x^2-12x=3x^3+9x^2-3x\)
\(-x^4-4x^3-6x^2-12x-3x^3-9x^2+3x=0\)
\(x^4+7x^3+15x^2+9x=0\)
\(x\left(x^3+6x+9\right)\left(x+1\right)=0\)
\(x\left(x+3\right)^2\left(x+1\right)=0\)
\(x=0;-3;-1\)